Di masa COVID-19, bagaimana cara melindungi diri sendiri dan orang lain? - Angham G Hadi; Mohammed Kadhom; Emad Yousif; Nany Hairunisa (Jurnal Biomedika dan Kesehatan, 2020)
Coronaviruses are a big identified group of viruses that could result in sickness in humans and animals. It was confirmed that many of these viruses caused respiratory diseases among humans and their symptoms range from popular colds to more serious diseases, such as the Middle East respiratory syndrome (MERS) and severe acute respiratory syndrome (SARS). The recently detected Coronavirus (called SARS-CoV-2) causes the COVID-19 pandemic, which causes a serious threat worldwide. There was no previous knowledge of this virus before the outbreak of Wuhan city in China in December 2019. However, there is progress in defining, understanding and dealing with this virus. In this review, we are focusing on the common questions regarding coronavirus transition and spread, and how to prevent the infection.